Time strategies in environmental innovation policy: the case of the mobile fuel cell and hydrogen infrastructure - Christian Sartorius (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2007)
Although fundamental innovations can make especially important contributions to the environmental soundness of economic progress, they are often impeded by path dependency and lock-in on the part of established technologies. Because the intensity of the latter effect changes in time, it is possible to identify and strategically use windows of opportunity - periods in which successful transition is greatly facilitated. In the case of the mobile fuel cell, economies of scale, learning and network effects are among the most important techno-economic determinants of such a window. Other more political determinants are political guidance and supranational agreements. All effects were combined to form a time strategy that allows innovation policy to effectively push the new technology at the lowest possible cost for the economy.
urn:nbn:de:0011-n-661569
Keywords: 330